ASSESSMENT OF PHYSICOCHEMICAL PARAMETERS IN NASAL FEEDING TUBES: Life Science-Environmental sciences - NASIBULLAH, MALIK; AHMAD, NASEEM; KUMAR PATEL, DEVENDRA; MASIHURRAHMAN (International Journal of Life Science and Pharma Research, 2012)
The main objectives of study were to evaluate the physicochemical test of the leachates of finished plastic biomedical devices; Ryle’s tube, four brands were used in the present study. At 60±2°C for 2h the maximum global migration residue was found from S4 sample in 0.9% sodium chloride (3.5 mg/100 ml) while the minimum was in S3 sample in 3% acetic acid (0.3 mg/100 ml) Figure 1. At 25±2°C for 24h the maximum global migration residue was found from S1 sample in 0.9% sodium chloride (2.3 mg/100 ml) while the minimum was in S3 sample in 3% acetic acid (0.1 mg/100 ml) Figure 2. At 60±2°C for 2h the maximum oxidizable materials was found from S1 sample in double distilled water while the minimum was in S4 sample in 0.9% sodium chloride (Figure 3). At 25±2°C for 24h the maximum oxidizable materials was found from S1 sample in double distilled water while the minimum was in S3 sample in 3% acetic acid (Figure 4). These additives are not chemically bound to the matrix of the polymeric materials and leach out during normal use